State Polytechnic Students’ Perception on General English Subjects - Iis Sulyaningsih (Jurnal Bahasa Inggris Terapan, 2019)
This paper discusses the Bandung State Polytechnic Students’ perception towards General English classes (General English 1 and General English 2). The research is aimed to investigate the students’ perception towards the materials given in General English 1 and General English 2 classes. The survey was carried out to 110 students from 2 engineering classes and 2 non-engineering classes. This research applied quantitative method that used questioners to gain the data. Thus, the data were analyzed by applying SPSS, and the result shows that students’ perception on General English1 subject is different from their perception on General English 2 subject.They perceive thatGeneral English1 subject provides important basic skill for communication in English, however it needs improvement in some materials for there are some students doubt about it.  On the other hand, students think that the materials in General English 2 do not reach their needs and expectations. Accordingly, General English in Bandung State Polytechnic needs to be developed. Keywords: English, General English, Polytechnic Curriculum